Pomiędzy tradycją a prawem: sytuacja hinduskich kobiet w Indiach - Nowicka, Urszula (PRAWO i WIĘŹ, 2024)
Contemporary India is caught between its attachment to tradition and the demands of modern civilization for respect for human dignity. Despite the constitutional guarantee of equality before the law and the prohibition of discrimination based on gender, the shape and character of society are determined by religion and loyalty to tradition. The research problem of this paper is the situation of Hindu women in India; the author searches for the causes and possibilities of change in this situation. In pursuit of her research objective, she analyzes the Hindu tradition to find sources that define the role of women; studies the actions taken by the Indian government to be able to assess the relevance and effectiveness of the state policy; interprets data that reflect the everyday life of Indian women to show that the problem is not only theoretical but requires a specific response, which is postulated in the conclusions.